Pharmacological Evaluation of Novel Isonicotinic Carboxamide Derivatives as Potential Anti‐Hyperlipidemic and Antioxidant Agents. Issue 10 (24th August 2017) - Abu Farha, Rana; Bustanji, Yasser; Al‐Hiari, Yusuf; Bardaweel, Sanaa; Al‐Qirim, Tariq; Abu Sheikha, Ghassan; Albashiti, Rabab
Abstract : Hyperlipidemia and oxidative stress have been implicated as contributing factors to the development of atherosclerosis and cardiovascular diseases (CVDs). Currently, a large number of antihyperlipidemic medications are conveniently available in the market. Nonetheless, the majority of antihyperlipidemics lack the desired safety and efficacy. Thus, the present study was undertaken to evaluate the potential effect of novel N ‐(benzoylphenyl)pyridine‐4‐carboxamide and N ‐(9, 10‐dioxo‐9, 10‐dihydroanthracenyl)pyridine‐4‐carboxamide derivatives in controlling hyperlipidemia and oxidative stress using the Triton WR‐1339‐induced hyperlipidemic rat model for antihyperlipidemic activity and the DPPH radical scavenging assay for antioxidant activity. This study revealed the antihyperlipidemic activities of some of the newly synthesized, novel carboxamide derivatives, mainlyC4 andC12 ( p  < 0.05). The majority of the compounds displayed a relatively low or no DPPH radical scavenging effect, withC20 possessing the best radical scavenging effect (22%) among all. This research opens the door for new potential antihyperlipidemic compounds derived from isonicotinic acid. N ‐(3‐Benzoylphenyl)pyridine‐4‐carboxamide (C4 ) was found to have promising lipid‐lowering and antioxidant effects, which may create a protective effect against CVDs, by reducing the LDL‐C levels and diminishing the generation of reactive oxygen species. Abstract : Novel N ‐(benzoylphenyl)pyridine‐4‐carboxamide and N ‐(9, 10‐dioxo‐9, 10‐dihydroanthracenyl)pyridine‐4‐carboxamide derivatives were studied for their activities in controlling hyperlipidemia and oxidative stress. N ‐(3‐Benzoylphenyl)pyridine‐4‐carboxamide showed promising lipid‐lowering and antioxidant effects, which may provide protection against cardiovascular diseases.